Prognosis of COVID-19 Using Artificial Intelligence: A Systematic Review and Meta-analysis - Saeed Reza Motamedian; Negin Cheraghi; Sadra Mohaghegh; Elham Babadi Oregani; Mahrsa Amjadi; Parnian Shobeiri; Niusha Solouki; Nikoo Ahmadi; Yassine Bouchareb; Arman Rahmim (Frontiers in Biomedical Technologies)
Purpose: Artificial intelligence (AI) techniques have been extensively utilized for diagnosing and prognosis of several diseases in recent years. This study identifies, appraises and synthesizes published studies on the use of AI for the prognosis of COVID-19.